Mothers' lived experiences of giving medicines to children with severe and profound intellectual disabilities - DOYLE, CARMEL ANNE (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2019)
Background. Summary. Children with severe and profound intellectual disabilities experience multiple chronic health conditions that require a large variety and number of medicines. Mothers take on the responsibility of giving medicines on a daily basis with their child with severe and profound intellectual disabilities. There is a dearth of literature pertaining to this phenomenon and therefore the impetus for this research was borne out of not only a personal interest but a clear lack of recognition and understanding of the essence of mothers lived experience. No comparable work was located and this research study was developed to illuminate the topic. Aims and objectives. The overall aim of this study was to explore mothers lived experience of giving medicines to children with severe and profound intellectual disabilities. The range of activities mothers undertake were identified and associated challenges highlighted. It was clarified how mothers learn to give medicines and the meaning of the phenomenon was explicated in order to demonstrate an understanding that might have implications for both families and children with severe and profound intellectual disabilities and healthcare professionals providing services also. Methodology. A hermeneutic phenomenological approach guided by the work of van Manen (1990) underpinned this research study and focused on interpreting and understanding what it means for mothers to give medicines to their child with severe and profound intellectual disabilities. On gaining ethical approval, purposeful sampling was adopted to include 15 mothers of children with severe and profound intellectual disabilities who experienced the phenomenon. Multiple in-depth face to face interviews and participant diaries were utilised for data collection. Van Manen s method for thematic analysis was used to analyse the data and extrapolate the key essential themes. Findings. The findings provided an integration of the views of participants whether gathered through interview or diary. Findings presented were supported with direct quotations to reinforce the issues under consideration. A total of 20 essential themes were identified through the process of hermeneutic data analysis and presented using the five existential dimensions endorsed by van Manen (1990). An array of activities was evident in terms of giving medicines with insight given into the key relationships mothers experience in their role and the resultant impact these have on daily life. Furthermore, the challenges mothers experience in giving medicines and knowing and learning key associated skills were expounded. Both the physical and emotional bodily experience of giving medicines was explored with dominant feelings identified. The dimension of time provided an understanding of mothers daily lives with the concept apparent in all of the mothers undertakings. Being organised was identified as paramount to coping with the unpredictability of care. Additionally, the material things that influenced mothers experience of giving medicines were associated medicine equipment, documentation and the cost of medicines. A richer, deeper understanding of the phenomenon was depicted and it was determined that mothers experience of giving medicines to their child with severe and profound intellectual disabilities is a relentless and challenging, yet invisible element of caring. Conclusions. This study provides insight into the phenomenon of mothers lived experience of giving medicines to children with severe and profound intellectual disabilities. The adoption of hermeneutic phenomenology and presentation through existential dimensions makes it possible to understand the phenomenon as a human experience shared by the participants. It has captured what the lifeworld of these mothers looks like and has identified the challenges experienced by them in giving medicines . The findings and in- depth discussion and interpretation of these resulted in identification of implications and recommendations for research, education, practice and service provision. Through addressing the gap in understanding and exploring the meaning of this phenomenon it may be useful in developing care for mothers and children with severe and profound intellectual disabilities.
APPROVED
Keywords: Medicines and children; Children and intellectual disabilities